Dual‐templates molecularly imprinted monolithic columns for the evaluation of serotonin and histamine in CEC. Issue 9 (12th April 2013) - Zaidi, Shabi Abbas
<x xml:space="preserve">Abstract</x> To extend the application of molecularly imprinted polymers, the dual‐templates molecularly imprinted monolithic columns were developed in a capillary format. Two templates serotonin and histamine were simultaneously imprinted using two different functional monomers such as methacrylic acid (MAA) and methylenesuccinic acid (MSA) in a mixture of ethylene glycol dimethacrylate (EDMA) as a cross‐linker and AIBN as polymerization initiator dissolved in DMF as porogen. The resulting molecular imprinted polymers (MIPs) were characterized based on their performance in the CEC separation of two imprinted templates. The optimization parameters such as pH, ACN composition, and concentration of the eluent were varied to achieve best resolution and efficiency for CEC separation of templates with each MIP column. It was found that the MIP monolith column fabricated using MSA offered better resolution and separation efficiency compared to column fabricated with MAA. This work utilized the dual‐templates imprinting approach successfully and broadens the scope of multi‐templates imprinting capabilities in capillary format in CEC application.